Leg stiffness, valgus knee motion, and Q-angle are associated with hypertrophic soft patella tendon and idiopathic knee pain in adolescent basketball players - Satkunskiene, D.; Mickevicius, M.; Snieckus, A.; Kamandulis, S. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Knee pain without knee degenerative symptoms is a common phenomenon among young basketball players. The aim of this study was to identify factors predisposing young basketball players to suffer from knee pain. METHODS: The study involved 20 male adolescent (14-15 years) basketball players who were divided into two equal groups based on knee pain symptoms. Legs torque was tested on an isokinetic dynamometer. The length, elongation and the cross-sectional area (CSA) of the patellar tendon were measured with ultrasonography. Quadriceps angle (Q-angle), knee valgus motion, and joint angular displacement in the sagittal plane were analyzed using video recording during countermovement jump. Ground reaction force was measured using a force platform. RESULTS: Knee pain (KP) participants had a significantly lower Q-angle (P=0.045) and lower maximum varus knee angle (P=0.035), and a greater knee inside displacement (P=0.039) during squat phase. In the KP group, the CSA at the top of the tendon was significantly greater than in the middle (P=0.006) and at the bottom (P=0.039). Absolute tendon stiffness (P=0.013) and Young`s modulus (P=0.034) were significantly lower in the KP group compared with controls. Leg stiffness during landing was significantly greater in the control group (P=0.015). CONCLUSIONS: Leg stiffness, valgus knee motion, and Q-angle are associated with hypertrophic soft patella tendon and idiopathic knee pain in adolescent basketball players.